Arbetsterapi genom innovativ välfärdsteknologi för att främja aktivitet och delaktighet för äldre personer i ordinärt boende - Alfvin, Susanne; Eriksson, Linda (2014)
Occupational therapists role is to promote participation in occupations of daily living [ADL]. Research shows that people aged over 65 and living in ordinary housing, will increase in the future. The occupational therapist needs to be abreast of the developments taking place to meet the need of innovative welfare technology, to promote occupations or older people in ordinary housing. The aim of this literature review was to describe and provide an overview of innovative welfare technology that can be used as an intervention to promote participation in the activity for older people in ordinary housing. Data collection was conducted through searches in databases accessible via Luleå university library. Nine articles met the inclusion criteria and were selected and analyzed. Data analysis resulted in three categories: "Innovative welfare technology for ADL, ""Innovative welfare technology for movement in housing and society", and "Innovative welfare technology for social interaction". The result of the literature review shows that there are innovative welfare technology that can be used by occupational therapists working with older people in ordinary housing, which can help to promote autonomy and independence, safety and security in occupation. The results also indicate that more research is needed in this area.Keywords: Occupational Therapy, Innovative welfare technology, Ordinary housing, Elderly people. Validerat; 20140520 (global_studentproject_submitter)